2017
DOI: 10.3390/ijms18040767
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Profiles for Human Pancreatic Cancer Discrimination

Abstract: This study evaluated the clinical use of serum metabolomics to discriminate malignant cancers including pancreatic cancer (PC) from malignant diseases, such as biliary tract cancer (BTC), intraductal papillary mucinous carcinoma (IPMC), and various benign pancreaticobiliary diseases. Capillary electrophoresis−mass spectrometry was used to analyze charged metabolites. We repeatedly analyzed serum samples (n = 41) of different storage durations to identify metabolites showing high quantitative reproducibility, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…It is well recognized that metabolomic can provide snapshots of physiological conditions in biological samples by acquiring qualitative and quantitative information of low‐molecular‐mass endogenous metabolites, and it has been applied to identify potential molecular biomarkers of various cancers . A previous study suggested that malignant cancers had markedly altered intermediate metabolites in metabolic pathways compared with nontumor tissue . In addition, Budhu et al found that metabolic profiles were significantly different among several cancer types, and those distinct metabolites or metabolic pathways in particular cancer types might be helpful to distinguish primary tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well recognized that metabolomic can provide snapshots of physiological conditions in biological samples by acquiring qualitative and quantitative information of low‐molecular‐mass endogenous metabolites, and it has been applied to identify potential molecular biomarkers of various cancers . A previous study suggested that malignant cancers had markedly altered intermediate metabolites in metabolic pathways compared with nontumor tissue . In addition, Budhu et al found that metabolic profiles were significantly different among several cancer types, and those distinct metabolites or metabolic pathways in particular cancer types might be helpful to distinguish primary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] A previous study suggested that malignant cancers had markedly altered intermediate metabolites in metabolic pathways compared with nontumor tissue. 22 In addition, Budhu et al 23 found that metabolic profiles were significantly different among several cancer types, and those distinct metabolites or metabolic pathways in particular cancer types might be helpful to However, an effective integration of metabolomic with transcriptomic data could better interpret results that could not be obtained from one single metabolomic dataset. 25 To date, numerous researchers have unveiled significantly altered pathways and the associated metabolites with high diagnostic accuracy through merging metabolomic and transcriptomic.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis of these blood metabolomics for PC has also been reported [15]. We also recently reported the diagnostic ability of serum metabolomics [16], indicating the spread of metabolomic change from PC cells to metabolites in blood vessels as well as a range of biofluids.…”
Section: Introductionmentioning
confidence: 84%
“…These metabolites are secreted from the tumor tissue and spread to surrounding tissues and blood vessels [ 5 ]. Therefore, the combination of polyamine or metabolites has been used for the development of non- or low-invasive screening, such as blood, urine, and fecal-based tests [ 8 , 15 , 16 , 17 , 18 , 19 ], to identify patients with CRC or polyps, a precursor of CRC. Elevated concentration of urinary N 1 , N 12 -acetylspermine of CRC has been consistently observed in various studies [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis of these blood metabolomics for PC has also been reported [ 18 ]. We also recently reported the diagnostic ability of serum metabolomics [ 19 ], indicating the spread of metabolomic change from PC cells to metabolites in blood vessels as well as a range of biofluids.…”
Section: Introductionmentioning
confidence: 99%